2020
DOI: 10.1186/s12943-020-01155-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation of mature microRNAs inhibits their functions and is associated with poor prognosis in glioblastoma multiforme

Abstract: Background: Literature reports that mature microRNA (miRNA) can be methylated at adenosine, guanosine and cytosine. However, the molecular mechanisms involved in cytosine methylation of miRNAs have not yet been fully elucidated. Here we investigated the biological role and underlying mechanism of cytosine methylation in miRNAs in glioblastoma multiforme (GBM). Methods: RNA immunoprecipitation with the anti-5methylcytosine (5mC) antibody followed by Array, ELISA, dot blot, incorporation of a radio-labelled meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 48 publications
0
73
0
1
Order By: Relevance
“…miRNAs are also common m 5 C substrates, and the methylation of mature miR-181a-5p results in the abolishment of its tumor suppressor effect and is negatively correlated with poor prognosis in GBM. Mechanistically, mediated by the complex comprising DNMT3a and AGO4 (a miRNA-induced silencing complex), miR-181a-5p methylation impedes the formation of the miRNA-181a-5p/mRNA BIM duplex, which was originally defined to induce apoptosis by interacting with antiapoptotic Bcl-2 or Bcl-xl [14]. As a result, reduced apoptosis, as well as enhanced proliferation and invasion, was observed in cancer cells.…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
See 3 more Smart Citations
“…miRNAs are also common m 5 C substrates, and the methylation of mature miR-181a-5p results in the abolishment of its tumor suppressor effect and is negatively correlated with poor prognosis in GBM. Mechanistically, mediated by the complex comprising DNMT3a and AGO4 (a miRNA-induced silencing complex), miR-181a-5p methylation impedes the formation of the miRNA-181a-5p/mRNA BIM duplex, which was originally defined to induce apoptosis by interacting with antiapoptotic Bcl-2 or Bcl-xl [14]. As a result, reduced apoptosis, as well as enhanced proliferation and invasion, was observed in cancer cells.…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
“…As a result, reduced apoptosis, as well as enhanced proliferation and invasion, was observed in cancer cells. In addition, as estimated by Kaplan-Meier analysis, the methylation level of miR-181a-5p is associated with a poor survival rate, suggesting the profound potential for attenuating m 5 C methylation and restoring normal miRNA function for cancer treatment [14].…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the transcription level of microRNAs was related to the tolerance and effectiveness of immunotherapy. Research of Cheray et al showed that many members of miRNA contain 5mc, and some fragments of cytosine residues could methylate miRNA, and inhibit the formation of miRNA/mRNA duplexes, resulting in the loss of the duplex's function of suppressing gene expression, and further led to the occurrence of glioblastoma multiforme (GBM) [22]. Explaining the interaction mechanism of miRNA and exosomes is also a hot topic.…”
Section: Discussionmentioning
confidence: 99%